KARAKTERISASI MORFOLOGIS Trichoderma spp. INDIGENUS SULAWESI TENGGARA - -, GUSNAWATY HS; TAUFIK, MUHAMMAD; TRIANA, LENI; -, ASNIAH (Jurnal Agroteknos, 2014)
This study aimed to determine differences in the morphological characteristics of isolates of Trichoderma spp indigenous of Southeast Sulawesi. The experiment was conducted at the Laboratory of Agro Technology, Unit of Plant Pest and Disease, Faculty of Agriculture, University of Halu Oleo, Kendari.  This study used 11 isolates of trichoderm indegenous of Southeast Sulawesi. Observation variables were macroscopic characteristics, including: colony color and form, and microscopic characteristics, including: form of conidiophores, fialid and and conidia.  The research results showed that the 11 isolates of Trichoderma spp indigenous of Southeast Sulawesi had different morphological characteristics. Types of  Trichoderma spp obtained out of the 11 isolates were T. hamantum, T. koningii, T. harzianum, T. polysporum and T. aureoviride. Keywords : characterization, indigenous Southeast of Sulawesi, Trichoderma spp.